2012
DOI: 10.1111/ene.12057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early prednisolone treatment on the generalization rate in ocular myasthenia gravis

Abstract: Our results agree well with previous studies on this issue. Taken together, published data indicate risk ratios for generalization of below 0.32 under corticosteroid treatment in comparison to untreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 16 publications
3
30
1
Order By: Relevance
“…Sommer et al 6 Previous studies have shown overall conversion rates of OMG to GMG of 50% to 64%. 2,4,12,13 Our series of OMG patients showed a much lower overall conversion rate of 20.9%, consistent with more recent retrospective studies reporting overall conversion rates ranging from 23% to 31%, 6,8,14,15 and this low conversion rate was observed in subjects with or without immunosuppressant therapy. Prior studies have emphasized the possible effect of immunotherapy on conversion rates.…”
Section: Discussionsupporting
confidence: 88%
“…Sommer et al 6 Previous studies have shown overall conversion rates of OMG to GMG of 50% to 64%. 2,4,12,13 Our series of OMG patients showed a much lower overall conversion rate of 20.9%, consistent with more recent retrospective studies reporting overall conversion rates ranging from 23% to 31%, 6,8,14,15 and this low conversion rate was observed in subjects with or without immunosuppressant therapy. Prior studies have emphasized the possible effect of immunotherapy on conversion rates.…”
Section: Discussionsupporting
confidence: 88%
“…We believe that the difference is not due to bias, since the distribution of ocular and bulbar versus the generalized symptoms EOMG was similar in both countries. One may speculate whether this difference derives from treatment differences between the two cohorts, such as early treatment with corticosteroids in purely ocular-manifested MG, thereby preventing conversion to a generalized disease [35] . On the other hand, variable frequencies for ocular MG are described around Europe (13-52%) [3,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the retrospective studies have indicated that the reduced rates of generalization in patients with OMG who were administered early corticosteroid treatment, it has not been confirmed with a randomized prospective controlled study, yet. 5,13,14 MG is an autoimmune, multifactorial, clinically broad spectrum of disease which is seen more frequent in females and related to the neuromuscular junction. It is commonly easy to diagnose if suspected, however it is also easy to be misdiagnosed.…”
Section: Figurementioning
confidence: 99%